Enantioselective monitoring chiral fungicide mefentrifluconazole in tomato, cucumber, pepper and its pickled products by supercritical fluid chromatography tandem mass spectrometry. (15th May 2022) - An, Xiaokang; Pan, Xinglu; Li, Runan; Jiang, Duoduo; Dong, Fengshou; Zhu, Wentao; Xu, Jun; Liu, Xingang; Wu, Xiaohu; Zheng, Yongquan
Highlights: SFC-MS/MS was initially developed for detection of mefentrifluconazole enantiomers. Enantioselective behaviors of mefentrifluconazole were evaluated in the greenhouse vegetables system and pickling process. S -(+)-mefentrifluconazole was preferentially degraded than R -(−)-mefentrifluconazole in pepper and pickling cucumber. Mefentrifluconazole were removed 89.2% in cucumber, and 30.8% in pepper after cleaning and pickling. Abstract: A fast, effective, and environmental-friendly method was developed for enantioseparation and analysis of mefentrifluconazole in vegetables based on supercritical fluid chromatography tandem mass spectrometry. The enantioselective behaviors of mefentrifluconazole enantiomers in tomato, cucumber, and pepper in the greenhouse, and pickled cucumber and pepper during processing were investigated. Mefentrifluconazole enantiomers could obtain baseline separation within 2 min. The average recoveries of all matrices ranged from 78.4% to 119.0%, with relative standard deviations less than 16.8% for two enantiomers. S -(+)-mefentrifluconazole was preferentially degraded in pepper, while there was no enantioselectivity in tomato and cucumber under field conditions. During processing, S -(+)-mefentrifluconazole was reduced preferentially than R -(−)-mefentrifluconazole in pickled cucumber and cucumber brine. Inversely, R -(−)-mefentrifluconazole degraded faster than S -(+)-mefentrifluconazole in pepper brine. But, no obvious enantioselectivity was observed in pickled pepper. The result of this study could contribute to a more accurate dietary risk assessment of mefentrifluconazole in vegetables and processed products.